Hosein festival - Sobrian, C. (Art Photo Studio, [Trinidad and Tobago], 2011)
The postcard shows a crowd following a float, called a Tadjah, during Hosay celebrations in Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Festivals--Trinidad and Tobago; East Indians--Trinidad and Tobago; Muslims--Trinidad and Tobago; Shiites--Trinidad and Tobago; Hosay